Formulation, Evaluation, and Stability testing of Polyherbal Antidiabetic Capsules - Kaur, Navjot; Sharma, Shailesh (International Journal of Pharmaceutical Investigation)
Background: The phytoconstituents of single plants are inadequate to produce the desired efficacy and results. The combination of various herbal drugs in a specific proportion will improve the therapeutic efficacy by simultaneously acting on multiple targets, leading to enhanced patient compliance and therapeutic outcome. The objective of the present study was to formulate a polyherbal dosage form and to evaluate its efficacy and stability. Materials and Methods: The polyherbal extract was prepared by mixing different alcoholic extracts of all four drugs in a ratio of 1:1:1:1. A total of six polyherbal formulations (PHF) prepared were and evaluated for their preformulation studies. The phytoconstituents present were determined through Fourier transformer Infra-Red spectroscopy evaluation. The drug was further filled into capsules of 000 size and checked for all the evaluation parameters of capsules. The drug was checked for stability studies under various conditions. Results: The PHF1 showed the best flow properties. The capsules showed a drug release of 94% in 30 min. The spectroscopic results suggested the presence of terpenes, tannins, phenols, and flavonoids in granules. The capsules were found to be stable in various types of lights but get degraded at 70% humidity and temperatures above 55°C. Conclusion: This releasing pattern of medication from their capsule shell in vitro can be used to anticipate the releasing sequence in vivo. The Polyherbal capsule was shown to be fairly stable in light, temperature, and humidity.
Keywords: Azadirachta indica leaves; Pterocarpus marsupium heartwood; Picrorhiza kurroa rhizomes; Withania coagulans berries and fruit coat; Stability study; Dissolution; FTIR.